TSH Prevents Bone Resorption and with Calcitriol Synergistically Stimulates Bone Formation in Rats with Low Levels of Calciotropic Hormones - Dumic-Cule, I.; Draca, N.; Luetic, A. T.; Jezek, D.; Rogic, D.; Grgurevic, L.; Vukicevic, S. (Hormone and Metabolic Research, 2014)
Thyroid-stimulating hormone exerts both antiresorptive and anabolic effects on bone remodeling in aged ovariectomized rats and thyroid stimulating hormone-receptor null mice, supported by clinical results demonstrating that low thyroid-stimulating hormone level is associated with increased bone loss. To further explore the effect of thyroid-stimulating hormone on bone metabolism we introduced here a rat model with removed thyroid and parathyroid glands to obtain low serum concentrations of thyroid and parathyroid hormone, calcitonin and 1,25(OH)2D3. Surgery resulted in hypocalcemia, low parathyroid and thyroid hormone, 1,25(OH)2D3, C-telopeptide, and osteocalcin serum level. Intermittent administration of thyroid-stimulating hormone resulted in a further decrease of serum calcium and decreased level of serum C-telopeptide due to the suppression of bone resorption, while in the same animals osteocalcin in serum was higher indicating an increased bone formation rate. A combination of thyroid-stimulating hormone and 1,25(OH)2D3 significantly increased the serum Ca2+, C-telopeptide and serum osteocalcin values. MicroCT analyses of the distal femur and proximal tibia showed that rats treated with 1,25(OH)2D3 alone or in a combination with thyroid-stimulating hormone had an increased trabecular bone volume, and enhanced trabecular bone quality. Biomechanical testing of the trabecular bone showed an increased maximal load for 105% and 235%, respectively, in rats treated with 1,25(OH)2D3 alone, or in a combination with thyroid-stimulating hormone. We suggest that thyroid-stimulating hormone independently of calciotropic hormones suppressed bone resorption and stimulated bone formation, while in combination with 1,25(OH)2D3 acted synergistically on bone formation resulting in an increased bone volume.
Keywords: thyroid hormones; bone mineral density; osteoblast